KAJIAN EKSPERIMENTAL PENGARUH BENTUK SUDU TERHADAP UNJUK KERJA TURBIN HELIK UNTUK SISTEM PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) - Andareas Wijaya Sitepu; Jorfri B Sinaga; Agus Sugiri (Jurnal Ilmiah Teknik Mesin, 2014)
Electric energy demand in Indonesia is currently growing and is still dominated by energy-based fossil fuels, such as petroleum and coal. Fossil fuels are not renewable energy, so that when exploited continuously then fossil fuel reserves will be exhausted. In addition there are also areas where geographical conditions which do not allow the electrical networks up to the community. It needs to be made an effort to supply electrical energy needs by utilizing existing and potential conditions on the area such as energy of water flow. One of the turbines that can be used to harness the energy of water flow is helical turbines. The parameters for the use of a turbine is one form of helical blades (NACA), where the form of the blades (NACA) it affects the style of the lift and drag forces helical turbines. On the research study was performed experimentally on effect shape of blade of the helical turbine blades form by varying the shape of turbine blades NACA 0020, 0025 and 0030 with number of blades as much as 3 pieces for each form of blades. From the results of testing the turbine efficiency is obtained by helical 33,97% on the operation of the turbine blades with NACA helical 0030 and water flow rate of 0.8 m/s with a given light load of 130 Watts.Keywords : water turbines, micro hydro, the helical turbine, water power.